A combined parahydrogen and theoretical study of H2 activation by 16-electron d8 ruthenium(0) complexes and their subsequent catalytic behaviour. - Dunne, J; Blazina, D; Aiken, S; Carteret, H; Duckett, S; Jones, J; Poli, R; Whitwood, A (2004)
The photochemical reaction of Ru(CO)(3)(L)(2), where L = PPh(3), PMe(3), PCy(3) and P(p-tolyl)(3) with parahydrogen (p-H(2)) has been studied by in-situ NMR spectroscopy and shown to result in two competing processes. The first of these involves loss of CO and results in the formation of the cis-cis-trans-L isomer of Ru(CO)(2)(L)(2)(H)(2), while in the second, a single photon induces loss of both CO and L and leads to the formation of cis-cis-cis Ru(CO)(2)(L)(2)(H)(2) and Ru(CO)(2)(L)(solvent)(H)(2) where solvent = toluene, THF and pyridine (py). In the case of L = PPh(3), cis-cis-trans-L Ru(CO)(2)(L)(2)(H)(2) is shown to be an effective hydrogenation catalyst with rate limiting phosphine dissociation proceeding at a rate of 2.2 s(-1) in pyridine at 355 K. Theoretical calculations and experimental observations show that H(2) addition to the Ru(CO)(2)(L)(2) proceeds to form cis-cis-trans-L Ru(CO)(2)(L)(2)(H)(2) as the major product via addition over the pi-accepting OC-Ru-CO axis.